PENGGUNAAN MEDIA PUZZLE GAMES UNTUK MENINGKATKAN AKTIFITAS BELAJAR PESERTA DIDIK DALAM POKOK BAHASAN IKATAN KIMIA DI SMA NEGERI 8 PEKANBARU - Faiza Ayesha; Jimmi Copriady; Sulismayati Sulismayati; Basri Anshari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2017)
This study is an action research (classroom action research) that uses two-cycle. The aim of this research is to improve the learning activities of students in chemical bonding topic in class X MIA 10 Senior High School (SMA) 8 Pekanbaru by using media Puzzle Games. Descriptive analysis is run for analyzing data. The instrument of this study using observation sheet activity. In the first cycle, the average percentage of students learning activity by 80% in both categories, a further meeting activity by 85% with very good category, the third meeting of 86.5% with very good category while the fourth meeting amoun ted to 89.40% with very good category. At the first meeting the activities of teachers percentage of 90.27% with a very good category, the second meeting amounted to 91.67% (excellent), the third meeting amounted to 93.05% (excellent), the fourth meeting amounted to 95.83% (excellent). The first cycle test results obtained an average of 84.05 while classical final test results of the second cycle of 95.83. Based on the analysis results there was an increase in the study of students from the first cycle to the second cycle. As for mastery learning of individual students, the first cycle refers to the Department of Education standards are 94.4% of students who completed school KKM standards while 88.8% of students who completed. In the second cycle by the Department of Education standards, completeness learners achieve 100% (complete), while for the standard 94.4% KKM school (complete). Thus, the results of studying chemistry in subject of chemical bonding can be improved students activities and achievement by using instructional media puzzle games.